Correlation of Coping Behavior and Social Support with Potential Bullying Action of Adolescent in the Working Area of Kesunean Community Health Center Cirebon City - Ouve Rahadiani; Bambang Wibisono; Muhammad Irsyad Baihaqi; Yunanda Ardian Prawiranata, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
with norms that can be carried out by a person or group of people who abuse the imbalance of power, where the aim of the perpetrator is to hurt the victim both physically and mentally. Coping strategies need to be developed by victims to overcome the stress experienced due to bullying. The social environment is a factor from outside adolescents which contributes quite a lot in determining their self-concept. Social support is thought to be one form of influence of the social environment on adolescents who are victims of bullying. This study aims to determine the relationship of coping behavior and social support to the potential of Bullying actions in adolescents. This study used an observational analytical research method with a cross sectional approach which aims to determine the relationship between coping behavior and social support for bullying in adolescents. There is a significant relationship between social support and the potential for Bullying actions (p = 0.005), there is a relationship between coping behavior and the potential for Bullying actions (p = 0.005) and the independent variable that most influences the dependent variable or the potential for bullying is social support (p = -0,068). There is a relationship between social support and potential Bullying actions and there is a relationship between coping behavior and the potential of Bullying actions.